Academic community's investment decision in sharia stock market: The impact of financial literacy - Mohammad H. Holle; Muammar W. Maruapey; Magfirah Karanelan; Rilan Abdul Syarif; Binti Nur Asiyah (al-Uqud : Journal of Islamic Economics, 2023)
This study aims to determine the impact of Islamic financial literacy on the academic community at IAIN Ambon in investing in the Islamic capital market. The research methodology uses interpretive qualitative techniques. Data were collected through observation and in-depth interviews with the academic community who became informants who were determined using the purposive sampling technique. The results of the study revealed that the academic community of IAIN Ambon has high financial literacy because they received special education through investment courses and special Islamic capital markets for students, and training for lecturers and other staff, but it has not had a maximum impact on investment decisions in the Islamic capital market. The reason is that the implementation and assistance from the results of education and training are not carried out optimally. Another cause is the level of income and risk that the community thinks so that it creates boredom to invest.